2010
DOI: 10.1097/aog.0b013e3181d04dff
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and Anal Incontinence During Pregnancy and Postpartum

Abstract: The occurrence of UI and anal incontinence during the postpartum period is related to the presence of incontinence in pregnancy, and vaginal delivery increases the risk of persistent incontinence. Some risk factors for both incontinences during pregnancy and postpartum are related to lifestyles and obstetric practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
132
3
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(165 citation statements)
references
References 27 publications
22
132
3
8
Order By: Relevance
“…A cohort study with 1,128 nulliparous pregnant women without previous UI in the first trimester of pregnancy identified a prevalence of 8.3% of UI (CI95% 6.6 -10.0) (18) , close to the percentage of 7.4% among the primigravidas in this study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A cohort study with 1,128 nulliparous pregnant women without previous UI in the first trimester of pregnancy identified a prevalence of 8.3% of UI (CI95% 6.6 -10.0) (18) , close to the percentage of 7.4% among the primigravidas in this study.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, the average (8.2; SD = 3.9) and the median (8) of the ICIQ-SF score showed values that were compatible with moderate impact on the quality of life of pregnant women with UI, considering the classification into four categories of severity: light (1-5), moderate (6)(7)(8)(9)(10)(11)(12), heavy (13)(14)(15)(16)(17)(18) and very heavy (19)(20)(21) (28) .…”
mentioning
confidence: 85%
“…Studies performed in Denmark and Spain (4,10) found a high association rate between UI in the postpartum and the type of childbirth and with the occurrence of UI during pregnancy. Similarly, a United States study (11) performed with 80 pregnant women with UI found that 44% of the participants continued incontinent after childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…Research states that pregnancy and childbirth increase the frequency of UI (4) . Although UI have negative effects on women's everyday lives, affecting their quality of life, most incontinent women consider it to be something normal and do not seek medical help (4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hormonal changes, occurred mainly from the second trimester of pregnancy, may cause changes in the connective tissues, influencing the support and continence mechanism 1 . As a result of these changes, there may be a reduction in support of the bladder neck and proximal urethra, predisposing pelvic floor (PF) dysfunctions 2,3 , which may become more prevalent as the pregnancy progresses and are associated with the pressure exerted by the fetal head on the bladder 4,5 . O'Boyle et al 6 observed a significant increase in urethral mobility in primigravidae, suggesting that physiological changes occur in the pelvic floor (PF) during pregnancy.…”
Section: Introductionmentioning
confidence: 99%